PENDAMPINGAN REMAJA MASJID SEHAT-SMART - RABANI - endang wahyuningsih; Syahbana Daulay (Universitas Muhammadiyah Klaten, 2023)
Adolescence is a critical period of rapid development, growth and maturation both physically, cognitively, emotionally and socially. During adolescence both boys and girls are able to develop abstractly and critically. They begin to form a sense of who they are and what role they play. Meanwhile social networks develop through the immediate family, environment, peers who play a bigger role in influencing the environment. The development of adolescents is very vulnerable to negative environmental, social and cultural influences which are risk factors for adolescents to get caught up in risky behaviors such as sexuality, HIV/AIDS and drugs that have an impact on their health conditions. Mosque Islamic Youth (RISMA) at Masjdi Al-Ikhlas Gumpang Kartasuro Residential Area was established with the aim of: (1) fostering empowerment and increasing the potential to always fear Allah SWT, (2) having Islamic insight, (3) prospering the mosque, and (4 ) carrying out TPA (Al-Quran Education Park) activities, RISMA Members at the Al-Ikhlas Mosque totaling 20 people. RISMA's empowerment in improving the quality of Islamic life can be seen in RISMA's activities, namely Tadarus Al-Quran, studies on Islamic holidays, such as Maulid Nabi, Isra Mi'raj, Eid al-Fitr and Eid al-Adha, Nuzurul Quran, and Islamic New Year. These activities foster RISMA's behavior in order to become a true Muslim. The attitudes that are trained in RISMA activities improve the quality of Islamic life, including in the quality of character are Sidiq, Fathanah, Amanah, and Tabligh, in the quality of Charity are activities that originate from the conscience who feel happy to preach at the mosque, always spreading benefits, kindness and love for others, and with a quality work ethic, RISMA's activities are able to educate RISMA to be a responsible, creative, dynamic person carrying out activities with good planning and on targetAbstract stands alone in writing, so writers should not use quotations in this section. Abstract should provide a concise and concise explanation to the reader about the problems, objectives, methods, and findings discussed in the paper. Through this information, readers are expected to be able to understand the content and contribution of the writing. Abstract written in a single paragraph (single paragraph) and not more than 200 words. Abstract written in Bahasa Indonesia and English.